Integrating Hygiene Promotion Into World Bank Projects : Experiences from Colombia and Peru - Florez, Rocío (World Bank, Washington, DC, 2014)
This report has been created to provide practical tools, tips, and methodologies for project leaders to integrate hygiene components into their projects. It builds on available evidence about the contribution of behavioral change programs to the reduction of diseases, in particular hand-washing with soap initiatives, which can benefit health, environment, water, sanitation, and education projects. Project leaders should view hygiene promotion as a behavioral change process rather than a unidirectional media or education campaign. The knowledge generated from the research, enabling environment assessments, and other tools can be utilized in the early stages of project design and throughout the project cycle. It is crucial to understand the local environment to ensure that behavior change is sustainable once the project cycle is complete. Awareness of the importance of hygiene will vary in each region; therefore, every project must start with different assumptions. Water and Sanitation Program (WSP) and other partners continue to generate positive examples and lessons learned and transfer knowledge. For example, the Global Public-Private Partnership for hand-washing with soap helps countries close the gap as they strive to meet the millennium development goals. The tools and guidelines referenced in this document do not offer a strict formula, however, and should be revised and adapted to the needs of each project. The door remains open for continuous learning and improvement.